STRATEGI PENCIPTAAN LAPANGAN KERJA PADA SEKTOR UMKM DI INDONESIA - Azhari, Azhari; Kamaruddin, Kamaruddin; Simahatie, Mai (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2024)
The contribution of the MSME sector to Indonesia's GDP and employment cannot be underestimated. This is evidenced by the fact that 64 million MSME businesses account for around 61% of the country's GDP and employ millions of people, this sector plays an important role in driving economic growth and creating job opportunities. However, in order for MSME businesses to continue to grow and contribute to the economy, it is important that they receive the support and resources needed to overcome challenges and seize opportunities in the global market. The purpose of this research is how to strategize MSMEs in job creation. This study uses descriptive qualitative analysis. Some of the strategies that can be taken in creating jobs in the MSME sector are increasing access to financing for MSME actors, tax incentives, increasing skill development programs for MSME entrepreneurs and encouraging innovation and technology adoption in the Indonesian MSME sector.